Gregarious Flowering of Aechmanthera Gossypina (Nees) Nees in Mussoorie Hills (Uttar Pradesh) - Biswas, SAS. (Indian Forester, 1973)
The gregarious flowering of Aechmanthera gossypina (Nees) Nees in Mussoorie hills is reported. The last published account of its gregarious flowering is by Duthie dated l890. The present record of the 1974 gregarious flowering and the studies through authentic herbarium specimens and relevant literature reveal that gregarious flowering is after twelve years. Field observations, economic aspects and general distribution are reported.